Digital Literacy and Digital Ethics of University Students in the Era of Artificial Intelligence: A Study at Universitas Islam Ahmad Dahlan Sinjai - Mytra, Prima; Danial, Danial; Qadrianti, Laeli (JTMT: Journal Tadris Matematika, 2025)
This study aims to describe the current state of digital literacy, digital ethics, and the utilization of Artificial Intelligence (AI) by students of Universitas Islam Ahmad Dahlan Sinjai. Amid the rapid development of AI technologies such as ChatGPT, Copilot, and similar tools, students are required not only to be proficient in accessing digital information but also to understand the ethical implications of using such technologies. This research employs a descriptive qualitative approach through in-depth interviews and observations involving 11 students from three faculties. The findings reveal that most students have utilized AI for academic tasks; however, their level of digital literacy varies, particularly in critical and ethical aspects. The study also found instances of digital ethical violations such as AI-based plagiarism and academic data manipulation. These findings emphasize the urgent need to strengthen digital literacy and ethics education within the university environment